INFORMATION SECURITY POLICY UPDATES AND INFORMATION SECURITY BREACH INCIDENTS OF SACCOS IN KENYA - Sirma, Jerotich; Raburu, George; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
The study analyzed the Impact of Information Security Policies on security breach incidences inKenyan Savings and Credit Cooperatives Societies (SACCOS). Information is an importantorganizational asset that that is mainly vulnerable to attacks from user error, hackers andcrackers, viruses and cyber criminals. This has resulted in loss of trillions of dollars around theworld and over 4 billion shillings in East Africa. The study investigated whether informationsecurity policies assist in preventing unauthorized individuals from accessing SACCOS’sensitive information. The study looked at the relationship between dependent and independentvariables. The dependent variable was incidences of security breaches while the independentvariables were investigation of the relationship between information security policy updates(frequency) and information security breach incidents. The results of the study revealed thatthere is a weak relationship between information security policies and security breach incidencesin the SACCOS sector. The study results hope to add to the body of academic knowledge andpractitioners in the SACCOS sector where information repository is a resource.